Librarians and social change: A systematic literature review - Apolinario, Rhea Rowena; Ahmad, Azree; Kadir, Irwan Kamaruddin Bin Abd (International Journal of Asian Social Science, 2024)
Throughout history, a constant component in the development of society is change, which often occurs within the social sphere and is referred to as social change. Social change involves and affects the lives of everyone subjected to it. For this reason, libraries and librarians have been more recognized in recent years for their contributions towards social causes and their potential as key players in social change. However, there still exists a gap in the understanding of their role and impact as likely fundamental contributors in social change. This study aims to address this gap through a systematic literature review which evaluates existing literature that centers on social change and libraries and librarians. The study aims to draw insights in the ways that libraries and librarians impact social change, and consequently influence library policies, practices, and discussions on the societal role of libraries. The reviewed literature revealed several trends of libraries and librarians being active contributors in social change, namely: libraries and librarians becoming recognized for their role as change agents in a continuously evolving society, and; the impact of having access to information and being knowledgeable in effectively applying it in a community could lead to improvements in different sectors. With better informed and better educated individuals, society can move forward towards an environment that provides equal opportunities and rights to all members, thus highlighting the positive and possible impact of libraries and librarians in supporting social change.